2020
DOI: 10.1101/2020.08.31.275644
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A deeply conserved miR-1 dependent regulon supports muscle cell physiology

Abstract: Muscles are not only essential for force generation but are also key regulators of systemic energy homeostasis1. Both these roles rely heavily on mitochondria and lysosome function as providers of energy and building blocks, but also as metabolic sensors2-4. Perturbations in these organelles or their crosstalk lead to a wide range of pathologies5. Here, we uncover a deeply conserved regulon of mitochondria and lysosome homeostasis under control of the muscle-specific microRNA miR-1. Animals lacking miR-1 displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 63 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…Gutiérrez‐Pérez showed that the main and conserved role of miR‐1 is to control several subunits of the V‐ATPase complex, which is ultimately essential to guarantee the assembly of this intricate complex in muscle cells. These results reveal a novel role for this microRNA in regulating protein complex assembly, and highlight the importance of mitochondrial function and proteostasis in muscle physiology 81 …”
Section: Maintenance and Perturbation Of Metabolic Networkmentioning
confidence: 74%
“…Gutiérrez‐Pérez showed that the main and conserved role of miR‐1 is to control several subunits of the V‐ATPase complex, which is ultimately essential to guarantee the assembly of this intricate complex in muscle cells. These results reveal a novel role for this microRNA in regulating protein complex assembly, and highlight the importance of mitochondrial function and proteostasis in muscle physiology 81 …”
Section: Maintenance and Perturbation Of Metabolic Networkmentioning
confidence: 74%
“…In contrast in C. elegans , most miRNAs are not required for viability in the lab, even at later stages [ 25 ]. This distinction between worms and mice likely reflects a difference in the tolerance of each organism to defects in the production of differentiated cells rather than generally distinct roles of miRNAs (e.g., miR-1-deficient C. elegans also show a range of molecular and cellular defects in muscles, but the animals are still fully viable in the lab) [ 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Precision of gene expression output is often difficult to control using transcription factors alone because transcription is an inherently noisy process 47 . Therefore, complex biological processes that govern development and cell differentiation in bilaterians recruited miRNA regulation to tune levels of dosage sensitive genes involved in these processes [48][49][50] . Two kinds of such miRNA-target modes of regulation are known: (1) coherent and (2) incoherent 51 .…”
Section: This Is In Contrast To Morphants Of Other Mirna Biogenesis F...mentioning
confidence: 99%